Women's legal consciousness in a poor urban community: finding order in and around the law - Harding, Joanne (Department of Public Law, 2022)
This thesis is a qualitative empirical study aimed at understanding the legal consciousness of women in a poor urban community. Through the narratives of women who were interviewed for this study, articles in the media, social media, and film, it explores the predominant problems experienced by women, and their experiences of engaging systems ‘in and around the law'. I argue that localities like Lavender Hill cannot be seen as homogenous and one cannot assume that all people approach problem solving from a similar perspective. Using a feminist lens, with literature on legal consciousness, legal cynicism, and legal pluralism as a backdrop, I describe the legal consciousness of poor urban women; what Ewick and Silbey refer to as ‘tracing the law in everyday life'. I interviewed 52 women, of which eight are women who live and work with other women in the community. Using an open ended questionnaire, I captured these narratives and analysed them, describing the themes and trends which surfaced. Poor urban women in this context not only navigate the daily threat of gang violence. They live in a place that is neglected, and seek positive solutions, despite high levels of patriarchy and systems that are inaccessible and unfair in response to their problems and disputes. A key finding of relevance to legal consciousness theory is the existence of different typologies of women − despite the relatively small geographic locality − with diverse norms and values. Of value is the description of varied attitudes towards systems ‘in and around the law', and different problem solving approaches. This makes a significant contribution to legal consciousness scholarship, in that it brings into view the seminal role of norms and values in social control, and how this shapes women's expectations of the law, as well as their approaches to the law, and other systems that assist with problem solving. This finding has value for practitioners and policy makers seeking to make a contribution to social justice and improve the lives of women in poor urban neighbourhoods like Lavender Hill.